Andean industrial policies during the commodity boom. Developmental or rentier States? - de la Cruz Prego, Fernando; Caria, Sara (Política y Sociedad, 2023)
The beginning of the 21st century offered two outstanding experiments in industrial policy in Latin America: the Bolivia of Evo Morales and the Ecuador of Rafael Correa. This work carries out a comparative analysis of both experiences by relating their models of international insertion and their effects on the institutional framework in charge of implementing industrial policies. The study concludes that the pattern of international insertion of these countries presents a bias towards the "resource curse", inhibiting the creation of institutions and industrial policies genuinely oriented to the promotion of productivity and international competitiveness, and promoting rentier behaviors in the public sector.